Risk Factors for Buruli Ulcer: A Case Control Study in Cameroon - Pouillot, Régis (Public Library of Science, 2007)
BACKGROUND: Buruli ulcer is an infectious disease involving the skin, caused by Mycobacterium ulcerans. This disease is associated with areas where the water is slow-flowing or stagnant. However, the exact mechanism of transmission of the bacillus and the development of the disease through human activities is unknown. METHODOLOGY/PRINCIPAL FINDINGS: A case-control study to identify Buruli ulcer risk factors in Cameroon compared case-patients with community-matched controls on one hand and family-matched controls on the other hand. Risk factors identified by the community-matched study (including 163 pairs) were: having a low level of education, swamp wading, wearing short, lower-body clothing while farming, living near a cocoa plantation or woods, using adhesive bandages when hurt, and using mosquito coils. Protective factors were: using bed nets, washing clothes, and using leaves as traditional treatment or rubbing alcohol when hurt. The family-matched study (including 118 pairs) corroborated the significance of education level, use of bed nets, and treatment with leaves. CONCLUSIONS/SIGNIFICANCE: Covering limbs during farming activities is confirmed as a protective factor guarding against Buruli ulcer disease, but newly identified factors including wound treatment and use of bed nets may provide new insight into the unknown mode of transmission of M. ulcerans or the development of the disease.